Intraseasonal characterization of tropospheric O3 in the North of the Buenos Aires Province: determining four months cycle and teleconnection evidence - Cionco, Rodolfo (2013)
Tropospheric ozone (O3T) is a secondary pollutant whose formation involved primarily solar radiation, NOx and volatile organic compounds. The North of the Buenos Aires Province (Argentina), has great agricultural-industrial activity; therefore, O3T study is an important issue in the area. In this paper, we present the first results tend to estimate and characterize O3T in San Nicolás de los Arroyos, North of Buenos Aires. Due to a lack of in situ data, we analyse the observations of the instrument OMI (Ozone Monitoring Instrument) of land remote sensing satellite AURA (GSFC/NASA). The data cover the years 2004- 2013. Applying the multitaper technique (MTM), very suitable for short and noisy data series, spectral analysis is performed on a grid corresponding 1° in latitude by 1.5° in longitude, centred South of the Province of Santa Fe. The most remarkable result is the emergence of a significant peak (95%) of four months cycle. To test the validity of this signal in San Nicolás, daily solar radiation data (Q) were analysed in the area. The application of MTM to the daily values of Q, yields a spectral peak of 120 days. It is concluded that atmospheric opacity on the site has four months variations that modify the solar radiation at the troposphere and consequently, the production rate of O3T. Evidence that these variations are due to teleconnection process originated in the Maritime Continent are presented.